Model WordNet Bahasa Indonesia berbasis Linked Data - Hendrik; Andhik Budi Cahyono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
WordNet is an online lexical database. In Computer Science domain, it plays important role in solving semantic interoperability issues. It also helps in many researches related to Natural Language Processing topic. Because of the importance of WordNet, there are many works to develop WordNet into several languages, e.g., Japanese, Arabic, and Indonesian. However, those are still not sufficient to address semantic interoperability issues. Therefore, there are several attempts to form WordNet into machine understandable format, i.e, Resource Description Framework (RDF) model. Still, there is no effort to form WordNet Bahasa Indonesia into RDF format. This paper presents the process of forming WordNet Bahasa Indonesia into Linked Data form. This process involves several phases, which are identifying data sources, data extraction, data transformation, data loading into relational database, and mapping database model into RDF model. The latest is done by using D2RQ framework, resulting the WordNet Bahasa Indonesia as Linked Data format. This data set is linked to WordNet-RDF of Princetown University.